Clinical and Epidemiologic Profile of Chronic Pancreatitis, A Retrospective Study in Eastern Nepal - Sharma, Rabin; Pradhan, Bikram; Karki, Prahlad; Subedi, Manish (Journal of Advances in Internal Medicine, 2018)
Background and Aims: Chronic pancreatitis is a condition characterized by chronic inflammatory and fibrotic changes in the pancreas leading to irreversible parenchymal damage and loss of glandular function. This retrospective study was conducted to study the clinic-epidemiologic profile of chronic pancreatitis in eastern Nepal. Methods: All adult patients admitted with chronic pancreatitis from June 2014 to June 2016 were included in this study. Data pertaining to demographics and clinical profile was obtained by retrospective chart review. Results: A total of (n=55) patients were enrolled in the study with a median age of 28 years. Idiopathic pancreatitis was the most common form of chronic pancreatitis (n= 37, 67.3%) and alcoholic chronic pancreatitis accounted for about a third of cases (n=18, 32.7%). Abdominal pain was a presenting symptom in all the cases (n=55,100%). Thirty-seven patients (67.3%) had diabetes mellitus. Ductal dilatation (n=55,100%) and calculi (n=43, 83.6%) were the most common findings on imaging using ultrasonography and Computed tomographic scan of abdomen). All the patients were receiving medical therapy. Most patients receiving medical therapy were on opioids (n=37, 67.3%) or pancreatic supplements (n=18, 32.7%). Complications were seen in only nine patients (16.4%). All of them had pseudocyst. Conclusions: In this study, idiopathic chronic pancreatitis (CP) was observed as the most common etiologic form of CP unlike CP related to alcohol use in other similar studies. CP related to alcohol use was seen as the second most common etiologic form. Diabetes was the most commonly associated comorbidity in our CP cohort. This study was performed in a small study population and is limited by several factors including statistical power. Larger studies are warranted to study the etiologic forms and outcomes of CP in Nepalese population.